Investigation of Different Modulation Formats Simultaneous Transmission in WDM Systems - Bobrovs, V.; Ivanovs, G. (Elektronika ir Elektrotechnika, 2010)
For a long time, intensity modulation (IM) format has been the dominant in wavelength division multiplexing (WDM) transmission systems. The major reasons for using were a relatively simple realization of optical transmitter and receiver compared with phase modulation (PSK) format. However, IM format has been less resistive to fiber nonlinearities. In recent years, as fiber optical communication is advancing to mixed signals broadcasting IM and PSK formats simultaneous transmission must be investigated.